The Concept of Universal Religion in Modern Hindu Thought - Sharma, A. author. aut Link
VIII, 173 p.
Keywords: Hindu thought has undergone a major reconfiguration in the nineteenth and the twentieth centuries, in response to its encounter with the forces of modernity. A key element in this reconfiguration is the perception of Hinduism itself as a universal religion; or, as a catalyst promoting the emergence of a universal religion, or, at the very least, as promoting religious universalism. This book examines the views of several major Hindu thinkers of this period, Swami Vivekananda and Mahatma Gandhi prominent among them, on this potent theme of modern Hinduism.